2015
DOI: 10.1080/02755947.2015.1017124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lake Surface Elevation on Shoreline‐Spawning Lost River Suckers

Abstract: We analyzed remote detection data from PIT‐tagged Lost River Suckers Deltistes luxatus at four shoreline spawning areas in Upper Klamath Lake, Oregon, to determine whether spawning of this endangered species was affected by low water levels. Our investigation was motivated by the observation that the surface elevation of the lake during the 2010 spawning season was the lowest in 38 years. Irrigation withdrawals in 2009 that were not replenished by subsequent winter–spring inflows caused a reduction in availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Samples of Lost River and Shortnose suckers are tagged each year with PIT tags to gather information on their behavior and survival following release (Janney et al 2008;Hewitt and Hayes 2013;Burdick et al 2015;Hewitt et al 2015). The PIT tags allow specific information to be linked to individual fish, such as species, size, age-class (adult, juvenile), and release location.…”
mentioning
confidence: 99%
“…Samples of Lost River and Shortnose suckers are tagged each year with PIT tags to gather information on their behavior and survival following release (Janney et al 2008;Hewitt and Hayes 2013;Burdick et al 2015;Hewitt et al 2015). The PIT tags allow specific information to be linked to individual fish, such as species, size, age-class (adult, juvenile), and release location.…”
mentioning
confidence: 99%
“…Even though the spawning season spanned multiple months, captures and encounters often occurred over much shorter time periods, with individual fish being fairly consistent from year to year in the relative times at which they joined the spawning aggregations (Burdick et al. 2015). All detections are classified without error, and tags are not overlooked when re‐encountered.…”
Section: Methodsmentioning
confidence: 99%
“…Sex affects p because males stay at spawning areas longer than females, thus increasing their probability of being encountered (Burdick et al. 2015). Time was important for p because of annual differences in sampling intensity and environmental effects on the condition of spawning habitats.…”
Section: Methodsmentioning
confidence: 99%
“…For the purposes of this study, we defined populations as groups of individuals that consistently spawn in the same location. Individuals from the two Lost River Sucker populations reside within the same lake; however, very few individuals switch from one spawning location to the other (Burdick et al 2015). We chose 50 y as a relevant time reference on the basis of the revised Recovery Plan for these species, which concluded that recovery was likely to require 30-50 y (USFWS 2013).…”
Section: Methodsmentioning
confidence: 99%